ABCB6, ABCB1 and ABCG1 genetic polymorphisms and antidepressant response of SSRIs in Chinese depressive patients. (November 2013) - Huang, Xiaoye; Yu, Tao; Li, Xin; Cao, Yanfei; Li, Xingwang; Liu, Baocheng; Yang, Fengping; Li, Weidong; Zhao, Xinzhi; Feng, Guoyin; Zhang, Xu; Dong, Zaiquan; et al.
Aim: Major depressive disorder is a common psychiatric disorder with worldwide prevalence. The most widely prescribed antidepressants are selective serotonin reuptake inhibitors (SSRIs). ATP-binding cassette proteins are responsible for the membrane transport of various molecules including antidepressive drugs. We investigated whether SNPs in ABCB6, ABCB1 and ABCG1 were associated with the treatment response of SSRIs.Materials & methods: A pharmacogenetic study genotyping nine SNPs was conducted in 290 major depressive disorder patients in the Chinese Han population. Allele and genotype frequencies were compared between responders and nonresponders.Results: The allele frequencies of rs28401781 and rs4148739 in ABCB1 showed significant difference between responders and nonresponders before correction (p = 0.0297 and p = 0.0359, respectively). No significant associations were detected for the ABCB6 or ABCG1 gene.Conclusion: Our results suggest that ABCB1 polymorphisms might be associated with SSRIs treatment response in the Chinese Han population. Original submitted 29 April 2013; Revision submitted 29 July 2013